Coronary Steal in a Patient With Apical Hypertrophic Cardiomyopathy: A Rare Case of Symptomatic Coronary Artery Fistula - Patel, Neil R (Cureus, 2020)
This report describes a rare case of multiple left coronary artery to pulmonary artery/left atrial fistulae causing a coronary steal phenomenon. A 58-year-old male with apical hypertrophic cardiomyopathy was seen in an outpatient office for exertional chest pain and dyspnea and subsequently had a positive exercise nuclear stress test. Coronary angiogram revealed 70-80% mid-left anterior descending artery stenosis with multiple proximal coronary artery to left atrial/pulmonary artery fistulae. Due to symptomatic coronary artery fistulae with coronary steal phenomenon, the patient underwent surgical correction of fistulae with bypass graft to left anterior descending artery. To our knowledge, this is the first case report on co-existing apical hypertrophic cardiomyopathy and coronary artery-left atrial/pulmonary artery fistulae. This article reviews current guidelines for management of coronary artery fistula.